The Semantic Equivalence of Culture Specific Terms in The English-Indonesian Translation of Novel The Duchess War By Courtney Milan - Navik, Susi; Hartono, Rudi; Sutopo, Djoko (English Education Journal, 2019)
This study aims to classifyand identify how the semantic equivalence of culture-specific terms achieved in English-Indonesian translation of novel The Duchess War. The aims then break down into five, following NewmarkÃ¢â‚¬â„¢s categorization of culture-specific terms; ecology, material, social, organizations, customs, and ideasand thelast is gestures and habits. The original novel investigated entitled The Duchess War by Courtney Milan and its translation entitled Ã¢â‚¬Å“Skandal Sang DuchessÃ¢â‚¬Âtranslatedy Eka Budiarti as the subject of this study. The limitation of this study covers up the semantic equivalence of culture-specific terms of the English-Indonesian translation of novel The Duchess Warby considering the seven types of meaning proposed by Leech (1974); conceptual, connotative, stylistic, affective, reflective, collocative, and thematic meaning.Descriptive qualitative research is employed in this study. The data gathered through 490 sentences containing culture-specific terms were identified and after reducing the redundancy of the data, researcher found there are 106 types of culture-specific terms and categorized into five categorizations following NewmarkÃ¢â‚¬â„¢s. The result shows of 106 culture-specific terms, there are 20,75% ecology culture, 39,62% of material culture, 16,04% of social culture, 21,70% of organizations, customs, and ideas, and the last is gestures and habits that has 1,89% of data.Based on the data, there are some similar culture-specific terms found based on the data gained. The same culture-specific terms categorization found, but the meaning is different, or the same in meaning but different in TT translation. Those happened because the translator considers the context in the usage of certain terms. All the data has been examined by the expert and the different meaning due to the suitable context in the novel The Duchess War. Hence, the culture-specific terms between ST and TT are semantically equivalent.